Less Invasive Vestibule Access Tunneling with Platelet-rich Fibrin Membrane for the Treatment of Gingival Recession - Krismariono, Agung (The journal of contemporary dental practice, 2019)
The aim of this study was to introduce the less invasive vestibule access tunneling in combination with platelet-rich fibrin (PRF) membrane for gingival recession treatment. Seven subjects with Miller's class I or II buccal gingival recession were selected for this study. All subjects were treated with mucogingival surgery using the less invasive vestibule access tunneling in combination with PRF membrane. Clinical examination performed on each subject and the height of gingival recession was recorded preoperatively (baseline), and at 1 and 3 months postoperatively. The data were statistically analyzed using analysis of variance (ANOVA) with Tukey's LSD test to determine the significant difference between groups. Statistical significance level was set at 0.05. The results showed that there were significant differences in recession height between baseline and both 1 month and 3 months postoperatively ( < 0.05). Nevertheless, there was no significant difference between 1 and 3 months postoperatively ( > 0.05). All patients reported satisfactory esthetic results both at 1 and 3 months postoperatively. Mucogingival surgery using the less invasive vestibule access tunneling in combination with PRF membrane for gingival recession treatment provided optimal root coverage. This article introduces a new tunnel technique in combination with PRF membrane for gingival recession treatment. Previous studies tried to make access using the tunnel technique performed through gingival sulcus. In this study, the access is performed through the vestibule region. Access from the vestibule can minimize the damage of gingival margin integrity, especially in patients with thin gingival biotype.